The role of the family in the process of political socialization a theoretical analytical study - عبدالكریم, م.م. شەهلا محمد عبدالكریم; عبداللە, آ.م.د. عبداللە خورشید عبداللە (Sulaimani Journal for Humanities, 2025)
Political socialization is an important part of the general socialization process of the individual within society. It aims to train and educate individuals so that they become good citizens who contribute positively to their communities. Through political socialization, individuals become aware of how to participate in political activities and affairs. This process begins in childhood and continues until adulthood, and it takes place through several social institutions, most notably the family, schools, political parties, the media, as well as friends and colleagues.The family is considered one of the most important of these institutions due to its fundamental role in shaping an individual’s political orientations, ideas, and beliefs, as it is the first environment in which a person learns values and concepts.Accordingly, this study highlights the significance of the family’s role in the process of political socialization as one of the key institutions in Kurdish society, responsible for instilling and teaching political ideas, beliefs, orientations, and affiliations, as well as fostering a sense of national belonging and patriotism.
Keywords: Family; political socialization